Peran Entrepreneurship Misional dalam Meningkatkan Kemandirian dan Efektivitas Pelayanan Yayasan Pintu Sinar Abadi Bandung Berdasarkan 1 Tesalonika 2:7-9 - Ulva Yuliarti; Timotius Sukarna; Maria Tititk Windarti (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
This research explores the role of missional entrepreneurship in increasing the effectiveness and sustainability of Yayasan Pintu Sinar Abadi's (YPSA) ministry in Bandung. Based on the principle of ministry described by the Apostle Paul in 1 Thessalonians 2:7-9, this article discusses how missionary entrepreneurship can optimise YPSA's financial independence and strengthen its social impact. Descriptive qualitative methods were used in this research, including in-depth interviews and field observations. The results show that a missional entrepreneurship approach improves the efficiency and effectiveness of social services in YPSA, as well as opening up more sustainable economic opportunities for the communities served.